Perjuangan Anak-Anak dalam Novel Si Anak Badai Karya Tere Liye - Ningsih, Okti Rahayu; Canrhas, Amril; Amrizal (Jurnal Korpus, 2022)
The purpose of this study was to find and understand the struggles of children in solving problems in the novel Si Anak Badai by Tere Liye. The research method used in this research is descriptive qualitative. The data collection technique used in this research is literature study. Based on the results of research that has been carried out on the story in the novel "Si Anak Badai" by Tere Liye, there are struggles of elementary school children such as their struggles in defending their homeland from eviction of port construction, their struggles to arrange tactics to reveal the truth, work hard, honest and unyielding. After doing research in this novel, there are four forms of children's struggles in the novel "Si Anak Badai" by Tere Liye. The form of children's struggles in Tere Liye's novel “Si Anak Badai” is like struggling to reach the ultimate goal, fighting power as compensation, striving for personal superiority, and striving for success